Adsorption Behavior of Charge Isoforms of Monoclonal Antibodies on Strong Cation Exchangers. Issue 12 (13th November 2017) - Steinebach, Fabian; Wälchli, Ruben; Pfister, David; Morbidelli, Massimo
Abstract : In this work, the adsorption behavior of the different charge isoforms of the same monoclonal antibody (mAb) on strong cation‐exchange resins is analyzed. While charge isoforms of the same antibody mainly differ in their effective charge, the similar structure and size allows developing a simplified model, which describes the adsorption behavior of mAb charge isoforms independently of the number of isoforms with only four parameters. In contrast to classical model‐based descriptions of the adsorption isotherm, the proposed work enables retrieving some physical meaning in the definition of the model parameters. These model parameters are determined for several resin‐antibody combinations. Thereby it is found that for mAbs on commercial cation exchangers an effective resin charge density of 0.22 ± 0.08 mmol mL −1 of solid phase is used for protein binding, which was found to be independent of the absolute resin charge density measured by titration. The presented results help to understand the adsorption behavior of mAbs on cation‐exchangers, which is applicable both for the isolation of the main charge isoform or for preserving a certain charge isoform pattern during the polishing processes. Abstract : The adsorption behavior of charge isoforms of monoclonal antibodies on strong cation exchange columns is analyzed. A simplified version of the stoichiometric displacement equilibrium model is introduced. The model reduces the number of fitting parameters from two for each charge isoform to 4 in total, independent of the number of isoforms while reducing the experimental effort. From results of different monoclonal antibodies on commercial strong cation‐exchangers, a consistent effective interaction group density of q 0 = 0.22 ± 0.08 mmol/mLsolid is found.